Towards a multitracer timeline of star formation in the LMC: I. Deriving the lifetimes of HI clouds - Ward, Jacob L.; Chevance, Mélanie; Kruijssen, Diederik; Hygate, Alexander P. S.; Schruba, Andreas; Longmore, Steven N. (Monthly notices of the Royal Astronomical Society, 2020)
The time-scales associated with the various stages of the star formation process remain poorly constrained. This includes the earliest phases of star formation, during which molecular clouds condense out of the atomic interstellar medium. We present the first in a series of papers with the ultimate goal of compiling the first multitracer timeline of star formation, through a comprehensive set of evolutionary phases from atomic gas clouds to unembedded young stellar populations. In this paper, we present an empirical determination of the lifetime of atomic clouds using the Uncertainty Principle for Star Formation formalism, based on the de-correlation of H alpha and HI emission as a function of spatial scale. We find an atomic gas cloud lifetime of 48(-8)(+13) Myr. This time-scale is consistent with the predicted average atomic cloud lifetime in the LMC (based on galactic dynamics) that is dominated by the gravitational collapse of the mid-plane ISM. We also determine the overlap time-scale for which both HI and H alpha emissions are present to be very short (t(over) < 1.7 Myr), consistent with zero, indicating that there is a near-to-complete phase change of the gas to a molecular form in an intermediary stage between HI clouds and HII regions. We utilize the time-scales derived in this work to place empirically determined limits on the time-scale of molecular cloud formation. By performing the same analysis with and without the 30 Doradus region included, we find that the most extreme star-forming environment in the LMC has little effect on the measured average atomic gas cloud lifetime. By measuring the lifetime of the atomic gas clouds, we place strong constraints on the physics that drives the formation of molecular clouds and establish a solid foundation for the development of a multitracer timeline of star formation in the LMC.